Mental Retardation Due To Congenital Hypothyroidism and Its Prevention - M. Suttan Assin (Paediatrica Indonesiana, 1984)
Thyroid hormone deficiency early in life causes severe and reversible brain damage. Fetal and neonatal hypothyroidism usually occurs in association with: a) Environmental Iodine deficiency producing endemic cretin b) Sporadic congenital hypothyroidism. In Indonesia 12 million people are suffering from endemic goiter and there are roughly 100,000 endemic cretins. Adequate Iodine supply in affected areas, which is now a National Health Programme, will diminish the birth of endemic cretins in the next decades. The sporadic congenital hypothyroidfsm (CHT) is due to anatomical abnormality or malfunction of the tyroid gland. If treated before the age of 3 months, fourfifths of the children will attain an IQ above 92. The only alternative is screening of all newborns for CHT, which is now a standard procedure in most of the developed countries. The incidence around the world is 1 : 3000- 4000 live births.